EDUCATIF IMPLICATIONS OF THE INTERPRETATION OF OLDER TERMIN THE QUR’AN PERSPECTIVE - Rahendra Maya; Ulil Amri Syafri; Budi Heryanto (Edukasi Islami : Jurnal Pendidikan Islam, 2021)
This article examines the educatif impilcation of the older term in Qur’anic verses that express through the interpretation of the commentators in their various popular works that are authoritative using a thematic interpretation approach (al-tafsîr al-maudhû’î) using qualitative methods of literature study with analysis descriptive-interpretative nature. The older term with various forms and derivations that were successfully identificated which later became the object and focus of this research were the term arba’în sanah, ardzal al-‘umur, al-shayb (al-syīb and al-shyaibah), al-shaykh (and al-syuyûkh), al-’ajûz, al-kibar (and al-kabîr), nu’ammir (yu’ammar and mu’ammar), and thâla or tathâwala al-’umur. After elaborating on the interpretation and accentation of its meaning and analyzing the results of the discussion, it turns out that these terms have many implications, especially those relating to aspects of Islamic education.